Afatinib and Necitumumab in EGFR-Mutant NSCLC with Acquired Resistance to Tyrosine Kinase Inhibitors - Nathaniel J. Myall, MD; Jennifer G. Whisenant, PhD; Joel W. Neal, MD, PhD; Wade T. Iams, MD; Karen L. Reckamp, MD; Sally York, MD, PhD; Lynne D. Berry, PhD; Yu Shyr, PhD; Leora Horn, MD; Heather A. Wakelee, MD; Sukhmani K. Padda, MD (JTO Clinical and Research Reports)
Introduction: Although tyrosine kinase inhibitors (TKIs) are effective against NSCLC harboring sensitizing EGFR gene mutations, acquired resistance is inevitable. Preclinical studies suggest that combining EGFR TKI and monoclonal antibody therapies may have activity in EGFR-mutated NSCLC that has progressed on TKI therapy alone. Therefore, we prospectively evaluated afatinib plus necitumumab in patients with EGFR-mutated NSCLC. Methods: This was a phase 1, dose-escalation, dose-expansion trial assessing the safety and efficacy of afatinib plus necitumumab. Patients had advanced or metastatic EGFR-mutated NSCLC with progression after (1) first-generation TKI if T790M negative, (2) subsequent line third-generation TKI if T790M positive, or (3) third-generation TKI in the first-line setting. Dose-escalation followed a 3+3 design. The primary end point of dose-expansion was objective response rate. Results: A total of 22 patients with EGFR-mutated NSCLC were enrolled. The maximum tolerated dose was afatinib 40 mg oral daily plus necitumumab 600 mg intravenous on days 1 and 15 every 28 days. There were no grade 4 to 5 adverse events observed, and seven patients (32%) experienced grade 3 treatment-related adverse events (three rash; one each oral mucositis, diarrhea, headache, ventricular arrhythmia, and tachycardia). In the entire cohort, there were no responses observed, the median progression-free survival was 1.8 months, and the disease control rate was 36% but varied between the subgroups. Conclusions: Afatinib plus necitumumab was safe but had limited activity in patients with EGFR-mutated NSCLC. Biomarker studies may identify patient subgroups that are more likely to benefit.